"Black Blowers of the Now": Jazz and Activism from King's Birmingham to Coltrane's "Alabama". (2nd January 2020) - Long, Barry
ABSTRACT: When Martin Luther King, Jr. described the "fierce urgency of now" at 1963s March on Washington, he at once drew upon a shared cultural memory and social consciousness. In a manner as much musical as rhetorical, Dr. King explicated his theme through a series of calls and responses on the riff, "now is the time." When poet and activist Amiri Baraka cited John Coltrane as the "black blower of the now" in his 1979 poem "AM/TRAK, " he asserted the saxophonist's contemporary cultural weight more than a decade after his passing. In ways similar to improvised performance, each example leverages the vitality and relevance of a forward-looking emphasis on "the now" against the blurred borders of jazz and spoken word. Coltrane's recording of "Alabama" less than three months after King's legendary speech marked a seminal confluence of journalism, rhetoric, and improvisation. This essay will explore John Coltrane's pivotal if involuntary role in shaping this changed dynamic in black activism and in particular, his incorporation of text as both inspiration and musical device.